Teaching method reading and comprehension of the text “Waves” (Sóng) by Xuân Quỳnh in the high school - Mai Hương, Nguyễn Thị (Institute of Education and Social Research, 2024)
Literature is an important subject in school education. Maxim Gorky, a famous Russian writer, once said that